APLIKASI PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS - Mahdiannoor Mahdiannoor; Nurul Istiqomah; Syarifuddin Syarifuddin (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
Maize crop (Zea mays L.) is one type of food crop seeds of the grass family. This plant is one of the important food crops, in addition to wheat and rice. The productivity of maize in Indonesia in general is still low, the cause other than packet proper cultivation and use of high yielding varieties impartial fertilization also not done. Along with organic farming, the use of various types of organic fertilizers both solid and liquid is also used to maize crop. This study aims to (i) to determine the liquid organic fertilizer application and (ii) determine the best dose of a liquid organic fertilizer application on the growth and yield of sweet maize. The research was conducted in the Nalui Village District of Jaro Tabalong Regency from May to August 2015. This study used a randomized group design (RGD) single factor. Factors studied were doses of liquid organic fertilizer by 5 treatments, namely: (p0) 0 cc.plot-1  (p1) 200 cc.plot-1  (p2) 400 cc.plot-1  (p3) 600 cc.petak -1 and (p0) 800 cc.plot-1  . The results of various doses of liquid organic fertilizer showed a significant influence on plant height at 28 and 35 days after planting (DAP), giving a significant influence on the cob weight, the length of the cob with husks and cobs without husks long. No effect on plant height at 14 and 21 DAP and leaf number aged 14, 21, 28 and 35 DAP. Liquid organic fertilizer dose of 800 cc.plot-1  gave the best growth and yield of the crop of sweet maize.